Translating intracellular calcium signaling into models - Thul, Ruediger (Cold Spring Harbor Laboratory Press, 2014)
The rich experimental data on intracellular calcium has put theoreticians in an ideal position to derive models of intracellular calcium signaling. Over the last 25 years, a large number of modeling frameworks have been suggested. Here, I will review some of the milestones of intracellular calcium modeling with a special emphasis on calcium-induced calcium release (CICR) through inositol-1,4,5-trisphosphate and ryanodine receptors. I will highlight key features of CICR and how they are represented in models as well as the challenges that theoreticians face when translating our current understanding of calcium signals into equations. The selected examples demonstrate that a successful model provides mechanistic insights into the molecular machinery of the Ca2+ signaling toolbox and determines the contribution of local Ca2+ release to global Ca2+ patterns, which at the moment cannot be resolved experimentally.